136k views
1 vote
P=−4b ^2+6b−9
Q=7b ^2−2b−5 ​
P − Q =

Answer is :−11b^2+8b−4

User Ninoska
by
6.0k points

2 Answers

6 votes

Answer:


\large\boxed{P-Q=-11b^2+8b-4}

Explanation:


P=-4b^2+6b-9\\Q=7b^2-2b-5\\\\P-Q=(-4b^2+6b-9)-(7b^2-2b-5)\\P-Q=-4b^2+6b-9-7b^2-(-2b)-(-5)\\P-Q=-4b^2+6b-9-7b^2+2b+5\qquad\text{combine like terms}\\P-Q=(-4b^2-7b^2)+(6b+2b)+(-9+5)\\P-Q=-11b^2+8b-4

User Maxie
by
5.9k points
2 votes

Answer:

see explanation

Explanation:

P - Q

= - 4b² + 6b - 9 - ( 7b² - 2b - 5) ← distribute by - 1

= - 4b² + 6b - 9 - 7b² + 2b + 5 ← collect like terms

= - 11b² + 8b - 4

User Rmcv
by
5.8k points